CEO Compensation, Strategy, and Firm Performance - Duong, Lien; Emanuel, D.; Truong, T.; van Dissen, J. (2019)
CEOs are increasingly being granted options as part of their compensation packages. However, despite all of the research conducted on executive compensation, there has been little investigation into the impact of CEO stock option grants on firm performance. In addition, many previous studies have found conflicting results on the impact of equity-based compensation on performance. Our study incorporates the competitive strategy adopted by the firm into its analysis. We document that a firm’s strategy impacts the level of stock options granted to the CEO. We also found that, after controlling for a firm’s competitive strategy, the relationship between CEO stock options and firm performance is stronger than when the sample is considered on a pooled basis.